2022
DOI: 10.1007/s11102-022-01207-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adult growth hormone deficiency and replacement therapy on the cardiometabolic risk profile

Abstract: Adult growth hormone deficiency (AGHD) is considered a rare endocrine disorder involving patients with childhood-onset and adult-onset growth hormone deficiency (AoGHD) and characterized by adverse cardiometabolic risk profile. Besides traditional cardiovascular risk factors, endothelial dysfunction, low-grade inflammation, impaired adipokine profile, oxidative stress and hypovitaminosis D may also contribute to the development of premature atherosclerosis and higher cardiovascular risk in patients with AGHD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 188 publications
1
14
0
2
Order By: Relevance
“…On the other hand, considering the strong association of afamin with WC, AST levels and measures of IR, higher afamin levels in long-term GH-deficiency are presumably associated with abdominal obesity, consequent insulin resistance and NAFLD. As afamin levels in GHS patients were found comparable to that of healthy controls (85.0 ± 25.5 vs. 80.3 ± 19.2, p=0.86), our study also supports previous findings ( 1 , 36 ) suggesting that GHRT could improve the cardiometabolic risk profile in patients with AGHD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, considering the strong association of afamin with WC, AST levels and measures of IR, higher afamin levels in long-term GH-deficiency are presumably associated with abdominal obesity, consequent insulin resistance and NAFLD. As afamin levels in GHS patients were found comparable to that of healthy controls (85.0 ± 25.5 vs. 80.3 ± 19.2, p=0.86), our study also supports previous findings ( 1 , 36 ) suggesting that GHRT could improve the cardiometabolic risk profile in patients with AGHD.…”
Section: Discussionsupporting
confidence: 91%
“…Growth hormone (GH) deficiency in adults is characterized by an unfavorable cardiometabolic risk profile ( 1 ) and shares common features with metabolic syndrome (MS) ( 2 ). In fact, both treated and untreated adult GH-deficiency (AGHD) are associated with increased prevalence of MS ( 3 ), which has been suggested to contribute to the increased cardiovascular morbidity ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Like other patients with hypopituitarism, treatment of SS patients with GH results in significant improvement in lipid parameters, lean body mass, endothelial function, arterial stiffness and exercise capacity (18,50,(56)(57)(58) resulting in improved mortality benefits (20). In one study, 14 patients of SS treated with GH for 18 months, resulted in improvement in body composition (like decrease WC and waist to hip ratio) and lipid abnormalities (like decrease in TC, LDL-C, TG and increase in HDL-C) (11).…”
Section: Effect Of Treatment On CV Risk Factorsmentioning
confidence: 99%
“…Many of these effects are attributed to low insulin-like growth factor-1(IGF-1), hypogonadism, untreated secondary hypothyroidism, and glucocorticoid (GC) overuse (11). These conventional (age and dyslipidemia) and nonconventional (increased inflammatory markers and leptin) risk factors promote cardiovascular (CV) diseases in the general population as well as in hypopituitary patients like those with SS (15)(16)(17)(18)(19). Studies published in late 1900, which also recruited patients with SS, suggested that hypopituitary patients have increased mortality than the general population and predominantly died of CV diseases with an overall standardized mortality ratio (SMR) of 1.99 (15,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with growth hormone deficiency in childhood present with lower BP, while due to premature aging of the blood vessels, and the increase of vascular stiffness in adulthood, they often develop hypertension. Giving patients with GH deficiency adequate substitution treatment significantly lowers blood pressure and reduces cardiovascular risk [61][62][63]. It is suspected that some vasoactive effects of GH may stem from central effects with a subsequent decrease in sympathetic outflow to vascular smooth muscle [64].…”
Section: Growth Hormone and Insulin-like Growth Factor-1mentioning
confidence: 99%